Student Career Planning at Al-Muqoddasah Islamic Boarding School Ponorogo - Herdiana Putri Indahsari (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
This study aims to determine the career planning of female students at the Al-Muqoddasah Islamic boarding school, Ponorogo district. The focus of this research is the factors that influence the career planning of female students at the Al-Muqoddasah Islamic boarding school, Ponorogo district. This study uses a qualitative approach with a phenomenological research design. The subject of this research is one female student in the low category and one female student in the high category as seen from the results of the career planning questionnaire. Data collection techniques using observation, interviews and documentation. Data analysis in this study was carried out with data reduction techniques, data presentation, verification and drawing conclusions. The result of this study is that the difference between the two subjects lies in the self-awareness of each individual to seek career information independently, and the spirit of oneself to prepare for his career.